Macular retinal nerve fiber layer thickness in retinitis pigmentosa patients with and without optic disc drusen - Steensberg, Alvilda H.; Malmqvist, Lasse; Bertelsen, Mette; Kessel, Line; Grønskov, Karen; Hamann, Steffen (Frontiers in Ophthalmology, 2024)
IntroductionRetinitis pigmentosa (RP) is a group of inherited retinal dystrophies characterized by progressive photoreceptor degeneration. In a recent study, we reported co-existing optic disc drusen (ODD) at 30%, a prevalence 15 times higher than in the general population. The aims of this study were to a) assess if macular retinal nerve fiber layer thickness (RNFLt) was increased in our cohort of RP patients and b) compare RNFLt between RP patients with and without ODD.MethodsIn this post-hoc analysis, optical coherence tomography (OCT) scans of patients with RP and healthy controls were manually delineated, and macular RNFLt measurements were obtained. The analyses were conducted both a) for RP patients without ODD compared to controls and b) for RP patients with and without ODD.ResultsOCT scans of 32 patients with RP and 13 healthy controls were included. Macular RNFLt was significantly increased in RP patients compared to healthy controls and in RP patients with ODD compared to RP patients without ODD.DiscussionFurther studies will explore whether increased RNFLt leads to ODD development through dystrophic calcification or, conversely, if ODD in combination with RP-associated retinal ganglion cell damage causes the increased RNFLt through retrograde axoplasmic stasis.